2012
DOI: 10.1002/nbm.2844
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical and experimental comparison of different techniques for B1 mapping at very high fields

Abstract: With the increasing use of ultrahigh-field MR with multiple transmit channels, mapping of the B₁(+) field has become a critical factor in many studies, leading to the publication of a large number of sequences for the measurement of the flip angle in recent years. In this article, the accuracy, precision and practicability of some of the most prominent of these techniques are investigated both theoretically, using error propagation computations and Monte-Carlo simulations, and experimentally for different sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 21 publications
4
83
0
Order By: Relevance
“…Although bias resulting from the spatial non-uniformity of the transmit RF transmit field is also well known and is commonly corrected by incorporating a B1+ map into the calculations (Helms et al, 2008; Yarnykh, 2010; Lutti et al, 2013; Stikov et al, 2015), the precision with which the B1+ map is obtained is typically ignored. Pohmann and Scheffler compared the precision of several B1+ mapping methods and found widely varying results depending on the method used and the nominal flip angle to be measured (Pohmann and Scheffler, 2013). Our results further demonstrate the necessity to consider the precision of B1+ mapping when using these to correct bias in the T 1 relaxation time maps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although bias resulting from the spatial non-uniformity of the transmit RF transmit field is also well known and is commonly corrected by incorporating a B1+ map into the calculations (Helms et al, 2008; Yarnykh, 2010; Lutti et al, 2013; Stikov et al, 2015), the precision with which the B1+ map is obtained is typically ignored. Pohmann and Scheffler compared the precision of several B1+ mapping methods and found widely varying results depending on the method used and the nominal flip angle to be measured (Pohmann and Scheffler, 2013). Our results further demonstrate the necessity to consider the precision of B1+ mapping when using these to correct bias in the T 1 relaxation time maps.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we used the AFI method for B1+ mapping, which was proposed and optimized by Yarnykh (Yarnykh, 2007, 2010) and has been shown to perform comparatively well (Pohmann and Scheffler, 2013). From Experiments 1–2 , we showed that increasing spoiler gradients makes the estimation of T 1 not only more accurate as previously reported (Yarnykh, 2010) but also more precise due to the complete spoiling of the transverse magnetization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase acquisition in both the conventional and the new methods can be quick; for example, a UTE [15] and a steady-state precession [37] sequence have been used for rapid conductivity mapping using phase acquisition alone. However, in order to map permittivity, or to improve the accuracy in conductivity, conventional methods require an additional B 1 + mapping scan.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the relationship between the MR image intensity and magnetic field map is non-trivial and specially designed MRI sequences exist to provide magnitude and phase magnetic field maps 23,24 . Such sequences usually target spatial profiles of H + 1 and H − 1 separately, which are the rightand left-hand polarized components of H 1 that correspond to transmit and receive sensitivity profiles of the rf coil respectively.…”
Section: Methods and Theorymentioning
confidence: 99%